Learning to never forget—time scales and specificity of long-term memory of a motor skill - Park, Se-Woong; Dijkstra, Tjeerd; Sternad, Dagmar (Frontiers in Computational Neuroscience, 2013)
Despite anecdotal reports that humans retain acquired motor skills for many years, if not a lifetime, long-term memory of motor skills has received little attention. While numerous neuroimaging studies showed practice-induced cortical plasticity, the behavioral correlates, what is retained and also what is forgotten, are little understood. This longitudinal case study on four subjects presents detailed kinematic analyses of humans practicing a bimanual polyrhythmic task over 2 months with retention tests after 6 months and, for two subjects, after 8 years. Results showed that individuals not only retained the task, but also reproduced their individual “style” of performance, even after 8 years. During practice, variables such as the two hands’ frequency ratio and relative phase changed at different rates, indicative of multiple time-scales of neural processes. Frequency leakage across hands, reflecting inter manual crosstalk, attenuated at a significantly slower rate and was the only variable not maintained after 8 years. Complementing recent findings on neuroplasticity in grey and white matter, our study presents new behavioral evidence that highlights the multi-scale process of practice-induced changes and its remarkable persistence. Results suggest that motor memory may comprise not only higher-level task achievement but also individual kinematic signatures.